Historical-pedagogical perspective of intellectual disability across the world and in Serbia - Đurić Zdravković Aleksandra A. (Zbornik radova (Univerzitet u Kragujevcu. Pedagoški fakultet u Užicu))
The perspectives on the conceptualization of intellectual disability throughout history have been highly variable. There was a long period of complete neglect of this condition, with the expansion of its study only beginning in recent history. The need to present a historical-pedagogical perspective of intellectual disability helps create greater criticality when it comes to creating the current rehabilitation process. This paper presents an account of events and personalities that transformed and advanced the concept of intellectual disability, according to the interpretation of contemporary ideologies, knowledge, and practices. Dealing with the first recorded structured concept of intellectual disability is associated with the name of the French psychiatrist Jean Itard and his extensive work with the "Wild Boy" Victor. Itard's legacy was dutifully carried forward by Édouard Séguin, who successfully navigated the challenging circumstances imposed by educational authorities. Despite numerous distractions imposed by the state, Séguin managed to create the first written literature that more precisely defined intellectual disability. He developed a stimulating program for individuals with intellectual disabilities and actively participated in the creation of international associations dedicated to intellectual and developmental disorders, which continue to address these issues today. Teodor Janković Mirijevski was the first Serbian pedagogist whose school reform legally enabled students categorized as "weaker learners" to participate in school activities on an equal basis with other students. Although in Serbia, historically, work on the conceptualization of intellectual disability was not so expansive, this reform was highly innovative, particularly considering the absence of similar ideas in the neighboring countries. In conclusion, various historical conceptualizations have led to a shift away from an approach based solely on deficits in functioning. Today, the favored approach is based on strengths, grounded in unequivocal research evidence.